Problems of financing sources for environmental protection in strategic documents of the European Union and Poland in the new financial perspective for 2021–2027 - Hajdys, Dagmara (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Over the past two decades, the world, and Poland with it, has faced a huge challenge of transforming its economy towards climate neutrality. The observed effects of climate change, such as abrupt weather changes (prolonged droughts, sudden downpours), increase in average temperatures, environmental pollution, call for systemic and social actions. It should be clearly noted that the responsibility for actions aimed at environmental protection is borne not only by public administration (central and local government), but also by the private sector, as the one using and influencing the environment. The year 2020 brought an unexpected global health crisis caused by the SARS-CoV-2 virus. MFF procedures developed up to that time were modified. The COVID-19 pandemic significantly affected the preparation of legislation, programs, and rules for obtaining funds from them for project implementation. Many legislative works have been postponed, causing delays. The fact of the pandemic has led to the implementation of the Instrument for Reconstruction and Enhancing Resilience, which includes large-scale financial support for public investments and areas such as green and digital projects, in addition to the regular financial perspective. Support will be provided in the form of loans (EUR 360 billion) and grants (EUR 312.5 billion). Aim: The aim of the study is to compare the financial instruments covered by the European Union financial perspectives 2021–2027 with 2014–2020 in the context of environmental funding sources in Poland. Results: Both in the financial perspective 2014–2020 and the new one for 2021–2027, environmental protection issues are one of the main priorities. The continuity of previous structural funds has been preserved and supplemented with new instruments in response to the unprecedented socio-economic situation that has arisen as a result of the global health crisis caused by the SARS-CoV-2 pandemic. As a result of negotiations, EUR 76 billion will be made available to Poland under the EU’s cohesion policy and the Fund for Equitable Transformation, whereas in the previous one the amount was EUR 85.2 billion. The allocation of funds and the directions of spending will not only result from Poland’s development needs, but also (and perhaps above all) from the modified priorities of the Union as a response to the health situation of the EU community after the pandemic and the continuation of existing activities related to research, innovation, digitization, climate and the environment. The launch of individual programmes will allow ongoing analysis and evaluation of both the solutions adopted in strategic documents and their effects.